Institutional barriers and policy opportunities for heirloom rice in Sabah: a preliminary analysis - Suffian, Faridah; Gunggut, Haijon; Joseph, Hendry; Suffian, Firdausi (Faculty of Administrative Science and Policy Studies, 2025)
The problem to be addressed in this article is linked to the limitations that hinder the sustainability and growth of heirloom rice within Sabah’s policy framework. As heirloom rice considered as a crop of high\ cultural and ecological value however, it remains underrepresented in the state’s agricultural context. Current agricultural policies prioritize high-yield commercial rice, thereby marginalizing heirloom varieties that lack formal support for financial, genetic, or market development. The objective of this paper is to analyse and discuss the institutional barriers that hinder the sustainability and growth of heirloom rice in Sabah. Using a qualitative approach grounded in institutional theory, data were collected through purposive sampling of key informants with expert knowledge and experience in the sector. Thematic analysis revealed four major barriers: (1) policy frameworks and institutional neglect that sideline heirloom rice, (2) limited prioritization within state agricultural agendas (3) weak market demand and fragmented value chains, and (4) structural barriers to farmer support, including infrastructure, incentives, and generational continuity.The study highlights the need for realigned institutional priorities, enhanced collaboration, and targeted support structures to integrate heirloom rice into Sabah’s agricultural framework. Policy reforms and dedicated support can foster sustainability, cultural preservation, and agricultural resilience within Sabah’s food systems.